Effects of Wet and Dry Finishing and Polishing on Surface Roughness and Microhardness of Composite Resins - Negin Nasoohi; Maryam Hoorizad; Seyedeh Farnaz Tabatabaie (Tehran University of Medical Sciences, 2017)
Objectives: This study aimed to assess the effect of wet and dry finishing and polishing on microhardness and roughness of microhybrid and nanohybrid composites. Materials and Methods: Thirty samples were fabricated of each of the Polofil Supra and Aelite Aesthetic All-Purpose Body microhybrid and Grandio and Aelite Aesthetic Enamel nanohybrid composite resins. Each group (n=30) was divided into three subgroups of D, W and C (n=10). Finishing and polishing were performed dry in group D and under water coolant in group W. Group C served as the control group and did not receive finishing and polishing. Surface roughness of samples was measured by a profilometer and their hardness was measured by a Vickers hardness tester. Data were analyzed using two-way ANOVA (P<0.05). Results: The smoothest surfaces with the lowest microhardness were obtained under Mylar strip without finishing/polishing for all composites (P<0.0001). The highest surface roughness was recorded for dry finishing/polishing for all composites (P<0.0001). Dry finishing/polishing increased the microhardness of all composites (P<0.0001). Conclusions: Dry finishing and polishing increases the microhardness and surface roughness of microhybrid and nanohybrid composite resins.